2014
DOI: 10.1128/jcm.00131-14
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of Candida kefyr in Patients with Hematologic Malignancies

Abstract: g Candida kefyr is an emerging pathogen among patients with hematologic malignancies (HM). We performed a retrospective study at Johns Hopkins Hospital to evaluate the epidemiology of C. kefyr colonization and infection in HM patients between 2004 and 2010. Eighty-three patients were colonized and/or infected with C. kefyr, with 8 (9.6%) having invasive candidiasis (IC). The yearly incidence of C. kefyr colonization and candidemia increased over the study period (P < 0.01), particularly after 2009. In 2010, C.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
45
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 59 publications
(53 citation statements)
references
References 35 publications
6
45
0
2
Order By: Relevance
“…Our center's experience over the last 5 years confirmed an increase in isolation of this species from patients with severe mucositis and neutropenia (19). Data generated in this analysis of FSC and bloodstream isolates reveal two important findings: (i) FKS1 HS1 mutations in C. kefyr are consistent with those in other Candida species that generate high-level echinocandin resistance, and these mutations render the GS enzyme complex as relatively resistant to drug inhibition in vitro; and (ii) a novel HS1 mutation confers relative resistance of C. kefyr to micafungin but preserves activity of the other echinocandin drugs.…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…Our center's experience over the last 5 years confirmed an increase in isolation of this species from patients with severe mucositis and neutropenia (19). Data generated in this analysis of FSC and bloodstream isolates reveal two important findings: (i) FKS1 HS1 mutations in C. kefyr are consistent with those in other Candida species that generate high-level echinocandin resistance, and these mutations render the GS enzyme complex as relatively resistant to drug inhibition in vitro; and (ii) a novel HS1 mutation confers relative resistance of C. kefyr to micafungin but preserves activity of the other echinocandin drugs.…”
Section: Discussionsupporting
confidence: 60%
“…This observation prompted a retrospective review of all C. kefyr infections in two major hematologic wards between 2004 and 2010 (19). Notable findings of that study included a striking seasonality in isolate recovery, with high rates during summer months.…”
mentioning
confidence: 99%
“…Overall, a higher proportion of C. tropicalis and C. krusei [7, 3134], C. kefyr [35], and sometimes C. glabrata [32] fungemia is found in hematology, and multi-species episodes are more frequent in oncology [36]. We and others evidenced the impact of preexposure to antifungals on the distribution of Candida species [22, 37, 38], and that duration of fluconazole exposure influences the risk of C. krusei fungemia in hematology [6, 39].…”
Section: Discussionmentioning
confidence: 99%
“…; Dufresne et al . ). In total, it was reported that 16% of candidemia cases were caused by this species in group of haematologic malignancy patients from 2009 to 2010, putting it the third most common species of candidemia (Pfeiffer et al .…”
Section: Discussionmentioning
confidence: 97%
“…; Dufresne et al . ). However, it should be noted that the aforementioned cases occurred nosocomially – these yeasts were not kefir‐originated and the patients were not associated with kefir consumption.…”
Section: Discussionmentioning
confidence: 97%